A new method for computation of positive realizations of linear discrete-time systems - Kaczorek, Tadeusz (Journal of Automation, Mobile Robotics and Intelligent Systems, 2021)
A new method for computation of positive realizations of given transfer matrices of linear discrete-time linear systems is proposed. Sufficient conditions for the existence of positive realizations of transfer matrices are given. A procedure for computation of the positive realizations is proposed and illustrated by an example.